Feat or futile: Students' perceptions of group work at a University of Technology in South Africa - Hall, I.; Erasmus, R.; Haywood, C. (South African Journal of Higher Education, 2022)
The increase in student enrolment at tertiary institutions in South Africa over the past few years has necessitated the need for group work without sacrificing the standard and integrity of education. Research has shown that group work offers many advantages to both lecturers and students. Interactive attributes such as teamwork, co-operation skills, leadership qualities, communication skills and confidentiality developed during group work are highly sought-after skills by prospective employers. This quantitative study aimed to determine whether students are positively or negatively inclined towards group work, as well as other possible factors influencing group work at a university of technology (UoT) in South Africa. A structured, close-ended questionnaire was administered to 309 students enrolled for the Applied Communication Skills course. The data were analysed using statistical methods. The results revealed that listening skills and mutual respect were crucial to develop good interpersonal skills needed for effective group work. When working in groups, students tend towards collectivism and negative aspects of group work, such as social loafing, are often overseen to maintain harmony and avoid direct confrontation with other individuals in the group. It was also found that male students agreed more strongly with negative conflict resolution than female students. Overall, the study showed that despite several negative aspects, students tended to be positively inclined towards group work.